The Influence of Socio-Economic Welfare on Stress Levels and Work Commitment of Personnel at the 1st Fleet Command of the Navy - Sigit Dandung Utomo; Ermaya Suradinata; Sampara Lukman; Ika Sartika (GoAcademica Research & Publishing, 2020)
The Indonesian Navy is part of the TNI military organization which has the high discipline and work commitment. However, it is not uncommon to find so many obstacles to personnel performance caused by mental stress or stress. The influence of social and economic welfare is one of the main factors causing increased stress which also affects the work commitment of Indonesian Navy personnel, Mako Koarmada I. This study aims to analyze the effect of socio-economic welfare on stress levels and work for commitment of Mako Koarmada I TNI AL personnel. This research uses quantitative methods. The quantitative approach itself uses the estimation technique of Structural Equation Modeling (SEM) and a literature review to explain the quantitative findings of this study. The results showed that the Social Welfare economy does not have a significant effect in reducing stress levels and increasing the work commitment of Indonesian Navy personnel at the 1st Fleet Command of the Navy.